2015
DOI: 10.3928/00989134-20151008-44
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Social Support and Self-Efficacy With Quality of Life in Older Adults With Diabetes

Abstract: Older adults are disproportionately affected by diabetes, which is associated with increased prevalence of cardiovascular disease, decreased quality of life (QOL), and increased healthcare costs. The purpose of this study was to assess the relationships between social support, self-efficacy, and QOL in a sample of 187 older African Americans (AA) and Caucasians with diabetes. Greater satisfaction with social support related to diabetes, but not the amount of support received, was significantly correlated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
43
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(58 citation statements)
references
References 48 publications
(63 reference statements)
12
43
1
2
Order By: Relevance
“…According to Bandura, selfefficacy affects people to reduce stress since any threatening conditions recognized as an experience that they can control over them (Bandura, n.d.). The finding of this study was in line with a previous study stated that perceived self-efficacy associated with quality of life domains (Amelia et al, 2018;Bowen et al, 2015;Kurnia & Kusumaningrum, 2017;Walker, Smalls, Hernandez-Tejada, Campbell, & Egede, 2014). People who perceived higher self-efficacy tend to be able apply diabetes management, including diet, regiment, and exercise requirement.…”
Section: Discussionsupporting
confidence: 92%
“…According to Bandura, selfefficacy affects people to reduce stress since any threatening conditions recognized as an experience that they can control over them (Bandura, n.d.). The finding of this study was in line with a previous study stated that perceived self-efficacy associated with quality of life domains (Amelia et al, 2018;Bowen et al, 2015;Kurnia & Kusumaningrum, 2017;Walker, Smalls, Hernandez-Tejada, Campbell, & Egede, 2014). People who perceived higher self-efficacy tend to be able apply diabetes management, including diet, regiment, and exercise requirement.…”
Section: Discussionsupporting
confidence: 92%
“…Although previous cross‐sectional studies identified a positive correlation between social support and QoL (Bowen et al., ; Rad et al., ), few longitudinal studies have explored the possible causal pathways. The results of this study supported that baseline social support can directly affect self‐care behaviors 6 months later.…”
Section: Discussionmentioning
confidence: 99%
“…A longitudinal research showed that social support could enhance the medication‐taking and physical activity behaviors in patients with T2DM (Nicklett, Heisler, Spencer, & Rosland, ). Social support has also been found to be associated with HbA1C levels and QoL (Bowen et al., ; Rad, Bakht, Feizi, & Mohebi, ). Moreover, a cross‐sectional study confirmed that social support is significantly associated with HbA1C levels through the mediation of self‐care behaviors (Osborn & Egede, ).…”
Section: Introductionmentioning
confidence: 99%
“…Family social support is an important factor towards improving self‐efficacy in the performance of certain behaviours. Available literature has supported the relationship between family support and self‐efficacy and their associations with improved self‐care behaviours among patients with chronic conditions (Bowen et al, ; Miller & DiMatteo, ).…”
Section: Introductionmentioning
confidence: 99%